The Role of Public Relations in Digital Era: Storytelling Strategy to Develop Corporate Reputation - Yunandika, Nike Putri; Bangun, Cendera Rizky Anugrah (UI Scholars Hub, 2024)
Storytelling can be a tool to create persuasive communication and provide personal engagement among its public. Storytelling strategy also can be applied in various digital communication channels, which is a flexible strategy to be implemented even in a niche digital business sector. Based on a rapid digital business competition, this study aims to discuss the use of storytelling strategy by Public Relations at DQLab.id, one of an active online Data Science Education Technology (Edtech) industry in Indonesia, as a tool to develop corporate reputation. The method used in this study is qualitative descriptive by providing depth interview, observation, supporting data, and literature study from various sources. The finding of this study shows that Public Relations practitioners at DQLab.id use Customer-Led Storytelling strategy combined with the use of keyword strategy on SEO to develop trust and leverage specific target markets. The result of this study also shows that the storytelling strategy used in DQLab.id has providing a different perspective of a story that increases the credibility of a message. Storytelling is a Public Relation’s tool that has significant leverage to help marketing activities by targeting the right customer segmentation, developing trust in a corporate brand, and deliver it into a positive reputation for DQLab.